FIDIC silver book : a companion to the 2017 EPC/turnkey contract, revised edition - Sørensen, Jakob B. (Emerald Publishing Limited, 2024)
FIDIC Silver Book is a practical guide for anyone involved in preparing, administering, or contributing to the FIDIC suite of contracts, 2017 edition. This revised edition responds to a number of recent developments including the 2022 amendments, further examples drawn from experience with the 2017 contracts, impacts of COVID-19 and the war in Ukraine, as well as guidance on use of FIDIC Contracts for projects using Building Information Modelling. Designed as a companion for both the first-time and also more experienced user the book presents an accessible guide to the 21 clauses of the 2017 FIDIC Conditions of Contract, using the Conditions of Contract for EPC/Turnkey Projects (Silver Book) as a basis. Opening chapters provide an introduction to the entire FIDIC suite of contracts. Part 2 provides a clause-by-clause introduction to each of the Clauses and Sub-Clauses in the Silver Book, and explain how they are interlinked. A final section includes a concise practical guide to the use of the FIDIC Conditions, and a summary of special provisions discussed in Part 2. Drawing on the author's 35 years' experience with the FIDIC Conditions of Contract, this accessible guide to FIDIC Silver Book provides an ideal introduction for first time users of the FIDIC conditions of contract and will also serve as a very useful handbook and practical commentary for more experienced users.